Impact of sustainability in fashion on consumer behavior and purchasing habits - Aleixo, Mafalda Figueiredo (2020)
With sustainability becoming one of today’s hot topics, people are increasingly committed to a greener lifestyle, with an eco-friendlier consumption and more conscious purchasing decisions. But is people’s sustainable commitment also evident in their fashion consumption habits? Thus, this research aims to analyze consumer behavior/attitudes towards sustainable fashion, identify the relevant factors considered in their purchasing decisions and if they are willing to spend more on sustainable fashion products. For such, an online experiment was conducted. Participants were randomly exposed to only one of three possible sustainability claims: footprint reduction, waste reuse and sustainability certifications, to understand if the various claims had a different impact on consumer behavior. Indeed, the results show that the sustainability certifications claim has a higher overall impact on consumers’ willingness to purchase sustainable fashion products than the other two claims. The consumers’ sustainable character (“Green”/“No-Green”) also influences their pro-environmental attitudes; “Greens” seem to be willing to pay more for sustainable products. The impact of the generational effect on the adoption of sustainable behaviors, addressed in this study, shows that there are practically no differences in the thinking and attitudes of different generations (Z, Millennials, X and Baby Boomers) towards sustainability. Although surprising, given past research on that particular topic, this result may be a starting point for deeper future research across generations. Nevertheless, one of the main take-aways is that companies must clearly and transparently communicate their sustainability claims, as this can have a positive effect on consumer attitudes towards the brand.